THE RISK FACTORS INFLUENCING ABORTION A LITERATURE REVIEW - Maya, Riska; Idiana, Adri; Yuniwati, Cut (Department of Midwifery, Health Polytechnic of Aceh, 2024)
Background: In general, the five leading causes of maternal mortality are bleeding, Hypertension in Pregnancy (HDK), infection, prolonged labor or obstructed labor, and abortion. Maternal mortality in Indonesia is still dominated by three main causes: bleeding, HDK, and infection. However, the proportions have changed, with bleeding and infection showing a tendency to decrease, while HDK has been on the rise. More than 25% of maternal deaths in Indonesia in 2017 were caused by HDK. Objective: This literature review aims to identify the risk factors influencing the occurrence of abortion. Method: This study employed a literature review method based on data from various electronic databases within the last five years, including Academic Search Complete, Proquest, Pubmed, EBSCO, and Google Scholar. A total of 7 articles were selected that met the criteria and were published in both Indonesian and English. Results: It showed a significant relationship between the age of pregnant women and the incidence of abortion (p<0.05). There is a significant relationship between parity and the incidence of abortion (p<0.05). A significant relationship exists between the distance between pregnancies and the incidence of abortion (p<0.05). There is a significant relationship between the mother's health history and the incidence of abortion (p<0.05). Conclusion: The factors causing the incidence of abortion include age, parity, pregnancy spacing, and the mother's health history. Preventive measures include avoiding pregnancy at a young age (<20 years) because, from a biological standpoint, the reproductive organs have not fully developed, and at an older age (>35 years), the elasticity of the pelvic muscles and surrounding area, as well as the reproductive organs, generally have diminished. Women in this age range are at a higher risk of experiencing antenatal complications, including abortion.